Effect of Various Slot Parameters in Single Layer Substrate Integrated Waveguide (SIW) Slot Array Antenna for Ku-Band Applications. - Moitra, S.; Bhowmik, P. S. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Extended study on SIW slot array antenna based on substrate integrated waveguide (SIW) has been proposed in this paper. Unlike recent publications, the effect of offset gap, gap between the slots and the gap between the last slot with the edge of the SIW antenna are extensively studied and effective formulation for proper positioning of the slots has been done. The structure consists of an array of slot antenna designed to operate in Microwave Ku Frequency bands. The basic structure is designed over a dielectric substrate with dielectric constant of 3.2 and with a thickness of 0.782 mm. The design consists of a SIW antenna fed with a microstrip to SIW transition. Multiple slot array effects are also being studied and analyzed using CST full wave EM Simulator. The designs are fabricated and supported with variation of return loss and radiation pattern characteristics due to appropriate slot offset. The analysis is being carried out to support integration to system-on-substrate (SoS) which promises more compact layouts.